Analisis Perbandingan Routing Protocol OSPFv3 dan IS-IS pada IPv6 - Jonathan Rovelano Huwae; Achmad Basuki; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
OSPFv3 and IS-IS routing protocols are routing protocols that are included in the type of link state routing protocol. In determining the best path, each routing protocol has different characteristics and algorithms. These differences will have an impact on how the work and results are different from the two routing protocols. This study used docker containers to simulate networks and implement routing protocols OSPFv3 and IS-IS with a hybrid topology. Both routing protocols will be implemented using IPv6 addressing. Testing will be carried out using 9 routers. The parameters to be used are the convergence time when the link is disconnected and the convergence time when the link reconnects. This study aims to determine the process of convergence when the link is broken and the process of convergence when the link is returned. This study showed that the OSPFv3 routing protocol has a faster convergence time than IS-IS in finding alternative paths when a link disconnection occurs. In 10 tests, OSPFv3 resulted in an average convergence time of 2046.55 ms compared to IS-IS whose average convergence time was 3686.74 ms. When linking back, the convergence value of IS-IS was faster with an average of 1843.08 ms compared to OSPFv3 with its average convergence time of 3891.16 ms.